THE POTENTIAL ANTIBIOTIC RESISTANCE OF OUTDOOR AIR BACTERIA IN LABORATORIUM KESEHATAN DAERAH JAWA BARAT - Yasmin Faadhilah, Tatia
Air is one of the most essential environmental components because human inhales 14 m3 air per day. Microorganisms could spread to the atmosphere which can lead to respiratory tract infection. Pathogenic microorganisms are commonly found in public health facilities and usually cause nosocomial infection. Excessive use of antibiotics for infection treatment could raise the amount of antibiotic resistant bacteria. Laboratorium Keseharan Daerah (Labkesda) Jawa Barat is a public health facility that is used for COVID-19 sample test and other laboratory test. Therefore, the amount of antibiotic resistant bacteria has to be evaluated. This research is conducted to determine (1) the existence of antibiotic resistant bacteria (2) the potential of resistance and minimum inhibitor concentration (MIC) from antibiotic resistant bacteria. The sample is taken from the outdoor area of Laboratorium Kesehatan Daerah Jawa Barat in the morning (08.00-12.00) and the evening (20.00-00.00). The method used for antibiotic resistance test is microdilution broth to four types of antibiotic which are ampicillin, amoxicillin, chloramphenicol, and ciprofloxacin with the variation of concentration (64; 32; 16; 8; 4; 2; 1; 0,5; 0,25; 0,125 ?g/ml). From the purification, there are 9 colonies that has been identified by the MALDI-TOF test. The antibiotic resistance results show that two species of bacteria that are resistant to ampicillin which are Bacillus clausii strain 01 and Klebsiella pneumonia with MIC value of 32 ?g/ml and 64 ?g/ml, respectively. Meanwhile, there are three species of bacteria that are resistant to amoxicilin which are Bacillus clausii strain 01, Klebsiella pneumonia, and Bacillus cereus strain 01 with the MIC value 32 ?g/ml, 64 ?g/ml, dan 32 ?g/ml, respectively. There are not any bacteria found resistant to ciprofloxacin and chloramphenicol. The resistant bacteria there is found it is not classified to Multi Drug Resistant Bacteria. There are two strain bacteria that could act as opportunist pathogen bacteria and cause infection which are Bacillus cereus 01 and Klebsiella pneumoniae. The existence of antibiotic resistant bacteria in an infection may be life threatening and has to be evaluated periodically to maximized therapeutic agent treatment.